Role of different polymer-stabilized metal nanoparticles in fluorescein reporter–based turn-off-on glutathione detection - Tiwari A.K.; Pandey P.C.; Narayan R.J. (My University, 2025)
In a fluorescence-reporter-based system, fluorescence quenching occurs when colloidal metal nanoparticles are added to fluorescein solutions owing to Förster resonance energy transfer (FRET) and the inner filter effect (IFE), depending on the physicochemical properties of the nanoparticles. This study examined the impact of various polymeric stabilizing agents on the fluorescence quenching behaviour of metal nanoparticles. Polyethyleneimine-stabilized gold nanoparticles exhibited superior fluorescence quenching of fluorescein due to strong dipole–dipole interactions, which led to FRET between the nanoparticle and fluorescein. Ligand exchange between loosely bound polyethyleneimine to the metal core and glutathione (GSH), in the presence of glutathione, led to fluorescence recovery. © The Author(s), under exclusive licence to The Materials Research Society 2025.